TASKS FACING THE SCHOOL PSYCHOLOGIST IN TERMS OF THE GENERAL EDUCATION CONCEPT (NATIONAL CURRICULUM) OF THE REPUBLIC OF AZERBAIJAN - Harun Oztash Halil,; Nizami Kadirov, (International Journal of Innovative Technologies in Social Science, 2022)
In accordance with the current curriculum reform, in addition to the theoretical and pedagogical problems of the curricula, the study of psychological problems is necessary in terms of identifying learning difficulties of young students. Psychologicalization of the concept of the education system is the main demand of the day. For this purpose, from the development of curricula and textbooks to the pedagogical process we face in this process, learning and mastering, pedagogical attitudes, joint activities, learning difficulties, etc. problems must be solved. “Currently, school psychologists are unaware of the content of subject curricula and find it difficult to provide necessary assistance to teachers in this area. Teachers, on the other hand, approach the problem from a purely pedagogical point of view and do not strictly follow the principle of individualization and differentiation of the learning process when assessing students' abilities. As a result, the development of skills necessary for the future life of the student is not provided enough.